2002
DOI: 10.1080/1044667021000003961
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Pre–Pro B Cells in the Bone Marrow of New Zealand Black (NZB) Mice: Implications for aDevelopmental Block in B Cell Differentiation

Abstract: Reductions in populations of both Pre-B cell (Hardy fractions D) and Pro-B cells (Hardy fractions B–C) have been described in association with murine lupus. Recent studies of B cell populations, based on evaluation of B cell differentiation markers, now allow the enumeration and enrichment of other stage specific precursor cells. In this study we report detailed analysis of the ontogeny of B cell lineage subsets in New Zealand black (NZB) and control strains of mice. Our data suggest that B cell development in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…Our data also revealed a slightly increased frequency in the occurrence of the most immature B-cell lineages, multipotent progenitor (MMP) and Pro-B cells in the bone marrow of Ly9 -deficient mice (data not shown), which is a variation that has been observed in other lupus-prone mice (36). …”
Section: Resultssupporting
confidence: 61%
“…Our data also revealed a slightly increased frequency in the occurrence of the most immature B-cell lineages, multipotent progenitor (MMP) and Pro-B cells in the bone marrow of Ly9 -deficient mice (data not shown), which is a variation that has been observed in other lupus-prone mice (36). …”
Section: Resultssupporting
confidence: 61%
“…In this study, a marked decrease in pax5 transcripts was observed in the RAG1-GFP + immature B-cell subpopulation of NZB RAG1-GFP mice compared with C57BL/6 RAG1-GFP controls, which implicates the alteration of gene transcription in this subpopulation in the resulting change in receptor editing activity during B-cell development in NZB mice. This is also supported by an earlier observation of pax5 gene expression in pre-pro B cells from the bone marrow of NZB and BALB/c mice [46]. A recent study examined the regulatory pathway activated following external stimulation mediated by the BCR-associated signal transduction molecules Ig-a and Ig-b.…”
Section: Discussionsupporting
confidence: 52%
“…This report presents our initial findings of defective B-lymphopoiesis in the auto-immune-prone fsn/fsn mice. Similar to other lupus-prone mice [10,13,22,23], early B-lymphocyte populations were found to be diminished with age in fsn/fsn mice resulting in a block or accumulation at the pro-B cell stage ( Figure 1, Table II). The decline in B-lymphocyte development correlated with changes in the cellularity of the bone marrow (Table I) and structure and organization of the bone marrow derived stromal cell population in culture (Figure 3).…”
Section: Discussionmentioning
confidence: 51%
“…The disruption of B-lymphopoiesis at the pro-B to pre-B cell transition is common among several strains of lupus-prone mice [10,11,13,23] indicating that this may be a common mechanism in B cell hyperactivation, auto-antibody production, and auto-immune disease development. In each of these cases, early senescence of B-lymphopoiesis occurs at a young age (between 2 and 3 months).…”
Section: Discussionmentioning
confidence: 99%